Você está na página 1de 10

g(x i ) f (x)

f(x) =

K

k=1

f k (x k ) .

, x n ) f k (x k )

x k

x

x = (x 1 , x 2 ,

g(x i )

g(x i ) =

{x}\x i

f(x) =

x

1

x

2

···

x i1 x i+1

··· f(x 1 , x 2 ,

x

n

,

x n ) .

{x}\x i

f (x 1 , x 2 ,

f x 1 x 2 x 3

, x n ) x i

g 1 (x 1 ) =

g 2 (x 2 ) =

{x 1 ,x 2 ,x 3 }\x 1

{x 1 ,x 2 ,x 3 }\x 2

f(x 1 , x 2 , x 3 ) =

x

2

f(x 1 , x 2 , x 3 ) =

x

1

x

3

x

3

f(x 1 , x 2 , x 3 )

f(x 1 , x 2 , x 3 )

g 3 (x 3 ) =

{x 1 ,x 2 ,x 3 }\x 3

f(x 1 , x 2 , x 3 ) =

x

1

x

2

f(x 1 , x 2 , x 3 )

x n f n x i f j x i f j g(x 1 , x 2 , x 3 , x 4 , x 5 )

g(x 1 , x 2 , x 3 , x 4 , x 5 ) = f A (x 1 )f B (x 2 )f C (x 1 , x 2 , x 3 )f D (x 3 , x 4 )f E

(x 3 , x 5 )

g

g(x 1 , x 2 , x 3 , x 4 , x 5 )

P (F, B, L, G, H) = p(X i |pa(X i )) = P (F )P (L|F )P (D|F )P (D|B)P (H|D)

i

µ xf µ fx µ xf µ fx f m x n x n υ e υ υ υ x e n(υ) υ

µ xf (x) =

hn(x)\{f }

µ hx (x)

µ fx (x) = f(X)

x\x

yn(f )\{x}

µ yf (x)  

X = n(f ) f

x µ xf (x) = 1 f µ fx (x) = f(x) e P (x)

P(x)

µ fx (x)

fn(x)

X E x

P(x|X E )

fn(x)

µ fx (x)

z s

z s =

f ·

d s

f D L O I = {I R , I L }

P (D, L, O|I) = P (I|D, L, O)P (D, L, O)

P(I)

y i x i i b i (x i ) y i b i (x i ) i

b i (x i ) = (x i , y i )

jN(i)

m j,i (x i )

Z N (i) i φ(x i , y i ) i y i m j,i (x i ) j i i m j,i (x i )

m j,i (x i ) = φ j (x j , y j )ψ j,i (x j , x i )

x

j

kN(j)\i

m k,,j (x j )

ψ j,i (x j , x i ) j x i x j x i